Computer networking a top-down approach - Kurose, James F. 1956-; Ross, Keith W. 1956- (Pearson, 2022)
For courses inNetworking/Communications. Motivate yourstudents with a top-down, layered approach to computer networking Unique among computernetworking texts, the 8th Edition, Global Edition, of the popular ComputerNetworking: A Top Down Approach builds on the authors' long traditionof teaching this complex subject through a layered approach in a ""top-downmanner."" The text works its way from the application layer down toward thephysical layer, motivating students by exposing them to important conceptsearly in their study of networking. Focusing on the Internet and thefundamentally importan